Sintering effects on mechanical properties of hydroxyapatite-titanium dioxide (HA-TiO2) composites - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
Composites of bovine bone derived HA with 5 wt% and 10 wt% of TiO 2 were sintered at different temperatures. Their characterization comprised measurements of density, microhardness, and compression strength together with SEM observations and X-ray diffraction analysis. Better densification behaviour was achieved at higher sintering temperatures. The highest microhardness value was measured in the samples sintered at 1300°C. The best compressive strengths of the samples containing 5% and 10% TiO 2 were obtained after sintering at 1300°C and 1200°C, respectively.
Keywords: Hydroxyapatite; Mechanical Properties; Sintering; Titanium Oxide